'Worthy to be hadde and redde of euerye Englishe man': the private, public and political contexts of Thomas More's English Workes. Issue 2 (27th September 2018) - Forsyth, Katherine
Abstract : In 1624 the playwright John Webster lauded Thomas More as a learned and worthy poet, placing him alongside Chaucer, Gower, Lydgate and Philip Sidney. It is clear that More was celebrated by Webster not only for the quality of his literary writing, but also for the wider political, social and historical influence of his literary output. This article uses the production of the 1557 folio of More's English Workes to explore the literary, political and religious influence of More's writing in the 1550s and beyond, and situates More's Workes within the wider context of folio production in Renaissance England. It also explores how the publication of More's Workes in folio established a distinct literary position for Thomas More in the mid-1550s, and highlights the unusual nature of the folio's compilation and production within the mid-Tudor book trade.